Body Mass Index Is Associated with Dietary Patterns and Health Conditions in Georgia Centenarians - Dorothy B. Hausman; Mary Ann Johnson; Adam Davey; Leonard W. Poon (Journal of Aging Research)
Associations between body mass index (BMI) and dietary patterns and health conditions were explored in a population-based multiethnic sample of centenarians from northern Georgia. BMI ≤20 and ≥25 was prevalent in 30.9% and 25.3% of study participants, respectively. In a series of logistic regression analyses controlled for gender and place of residence, the probability of having BMI ≥25 was increased by being black versus white and having a low citrus fruit, noncitrus fruit, orange/yellow vegetable or total fruit and vegetable intake. The probability of having BMI ≤20 was not associated with dietary intake. When controlled for race, gender, residence, and total fruit and vegetable intake, BMI ≥25 was an independent risk factor for diabetes or having a systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg, whereas BMI ≤20 was a risk factor for anemia. Given the many potential adverse consequences of under- and overweight, efforts are needed to maintain a healthy weight, even in the oldest old.